Building Peace through Poetry in the Fragile Context of Erstwhile FATA - Nizar Ahmad; Danish Mujahid; Tabinda Rani (Journal of Business and Social Review in Emerging Economies, 2022)
Purpose: The local peace actors, including poets, play an important role in promoting peace in a conflict context. In this vein, this study aims to investigate the role of local poets in promoting peace in the conflict-affected communities of Khyber Pakhtunkhwa, Pakistan